Reducing financial barriers through the implementation of voucher incentives to promote children's participation in community sport in Australia - L. J. Reece; C. McInerney; K. Blazek; B. C. Foley; L. Schmutz; B. Bellew; A. E. Bauman (BMC, 2020)
Abstract Background Participation in organised sport and physical activity contributes to health-enhancing levels of leisure time physical activity. In Australia, 58% of children aged 0-14 years participated at least once a week in October 2015 - December 2017. To overcome the frequently cited cost barrier, sports voucher incentives have been widely implemented across Australia. Method The financial value of jurisdictional vouchers and the National median financial value were used to calculate the proportion of total annual expenditure on children's participation in sport supported by sports vouchers. Participation rates using AusPlay data were estimated by age, sex and socio-economic index (SEIFA) at state and national level for children aged 0-14 years. Results Five States and Territories implemented sports vouchers from 2011 to 2018, with a median value of AU$150. Nationally, median annual expenditure for children's sport participation was AU$447 (IQR $194.2-936), with 27% reported expenditure supported by a sports voucher. The proportion of financial support from sports vouchers increased considerably with social disadvantage, rising to over 60% of total expenditure in the most disadvantaged populations. Conclusions Socio-economic status was associated with sports-related expenditure and sports participation amongst children. Sport vouchers should target children in the most disadvantaged areas to promote participation in organised sport and physical activity.